2016
DOI: 10.1038/srep34605
|View full text |Cite
|
Sign up to set email alerts
|

IGF-I induces senescence of hepatic stellate cells and limits fibrosis in a p53-dependent manner

Abstract: Hepatic fibrosis in nonalcoholic steatohepatitis (NASH) and cirrhosis determines patient prognosis; however, effective treatment for fibrosis has not been established. Oxidative stress and inflammation activate hepatic stellate cells (HSCs) and promote fibrosis. In contrast, cellular senescence inhibits HSCs’ activity and limits fibrosis. The aim of this study was to explore the effect of IGF-I on NASH and cirrhotic models and to clarify the underlying mechanisms. We demonstrate that IGF-I significantly amelio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 43 publications
4
100
0
2
Order By: Relevance
“…Besides, HGF and IGF‐1 play important roles in promoting hepatocyte proliferation and repairing tissue damage in the setting of liver injury. Moreover IGF‐1 can also decrease fibrosis and its expression was negatively associated with advanced fibrosis, which was consistent with a previous report . The hepatic tissue implant represents a promising alternative approach, notwithstanding the challenge in the time needed for cellular expansion in vivo.…”
Section: Discussionsupporting
confidence: 90%
“…Besides, HGF and IGF‐1 play important roles in promoting hepatocyte proliferation and repairing tissue damage in the setting of liver injury. Moreover IGF‐1 can also decrease fibrosis and its expression was negatively associated with advanced fibrosis, which was consistent with a previous report . The hepatic tissue implant represents a promising alternative approach, notwithstanding the challenge in the time needed for cellular expansion in vivo.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to its effects on growth and proliferation, reduced IGF‐I signaling has beneficial effects on longevity . Some reports demonstrated a cascade of IGF‐I action via ROS to induce cellular senescence in a p53‐dependent manner …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Nishizawa et al showed that administration of human recombinant insulin‐like growth factor 1 (IGF1) attenuates steatosis, inflammation, and fibrosis in mice treated to develop NASH or cirrhosis and drives HSCs to senescence. Importantly, these beneficial effects of IGF1 administration were not observed in p53‐deficient mice …”
Section: The Role Of Senescence In Nafld/nashmentioning
confidence: 96%